Immobilization of the Protease of Carica papaya on Activated Charcoal - Rafiq Khan, Mohammad; Bokhari, Hamim (Asian Journal of Chemistry, 2010)
Immobilization of the protease of Carica papaya was carried out on activated charcoal. A continuous immobilized enzyme proteolytic system was developed by packing a column with activated charcoal using citrate phosphate buffer pH 7.0. The percentage of immobilization was found to be 62.5 %. The column, of course, was partly chocked due to adsorption of casein with activated charcoal, which led to reduction in the flow rate. The life span of the enzyme immobilized on activated charcoal was 37 d.